Taboo Words in Bad Teacher Movie - Syahputri, Diani; Sari, Ambar Wulan; Siregar, Elfiyana Rosa (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The research deals with the study of sociolinguistic analysis In Bad Teacher Movie. The objectives of this study is to find out the types and the functions of taboo words used in Bad Teacher Movie The data was analyzed using a descriptive qualitative method. As a result, library research has been used to analyze the data. The data focused on the types of taboo words in Bad Teacher Movie. Based on the analysis, there were four types of taboo words in Bad Teacher Movie occurred in the namely Obscenity, Epithet, Vulgarity, and Profanity. From the data obtained, there were 32 data found in Bad Teacher Movie. There were Epithet 3 data (9%), Obscenity there were 19 data (59%), Vulgarity there were 5 data (16%), Profanity there were 5 data (16%). The functions of taboo words, there were four kinds of functions obtained in Bad Teacher Movie. To show contempt there were 14 data (44%), to draw attention to oneself there were 10 data (31%), to be provocative there were 7 data (22%) and to mock authority there was 1 data (3%).